Key markers of components of economic security of the state (Regional aspects of productive forces development of Ukraine, 2020)
Introduction. The article substantiates and proves the objective necessity of forming a system of vectors for assessing economic security, taking into account the transformational challenges of our time; certain trends in economic security and their key markers, which reflect modern transformation processes, namely: economic, technological, educational trends, socio-political, demographic and environmental. The proposed trends in economic security correspond to modern economic realities and develop the provisions of the concept of national economic security, taking into account new external economic and internal economic and socio-political conditions, challenges and threats to the functioning of the national economy.Goal. The goal of the article is to prepare trends in the approach to the formation of economic security of the state and their key signs that reflect modern transformation processes, namely: economic, technological, trend areas of education, socio-political, demographic and environmental.Results. The article states that during the last decade is actively developing and applies to the application of a risk-oriented approach to the formation of a system of economic security in one country. Within the risk-oriented approach, risks and their potential consequences are constructed by the system of combating danger precisely and the basis of such an approach. The peculiarity of the risk-oriented approach is that it takes into account not only the likely threats, but also the ability of the country to counteract such threats, identifying its potential vulnerability.Relationships between national security and economics increased as globalization and economic integration increased in recent decades. For open economies of the world, these interconnections are manifested as opportunities and possible threats to their national security. It is the definition of "risks vectors" that allows the channels of interactions between economic factors and national security. Relationships between national security and economics increased as globalization and economic integration increased in recent decades. For open economies of the world, these interconnections are manifested as opportunities and possible threats to their national security. It is the definition of "risks vectors" that allows the channels of interactions between economic factors and national security.